Examining emerging water quality markets through a collective action lens - Kraft, Katherine L., author; Cheng, Antony, advisor; Jones, Kelly, committee member; Stednick, John, committee member (Colorado State University. Libraries, 2018)
Water quality trading (WQT) is a collective action mechanism increasingly employed to address water quality concerns arising from nonpoint source pollution. Yet, many established WQT programs have experienced little or no trading activity. Collective action theory regarding common property resources (CPR) suggests that the external variables comprising a collective action institution's context dictate how effectively an institution can organize and perform. Because successful emergence is a precursor to successful performance and endurance down the road, understanding how and why external variables affect WQT collection action during early formative stages can provide insights into why some WQT programs may struggle to function and perform to their anticipated potential as they mature. However, few efforts have empirically examined WQT programs in terms of the external variables known to influence CPR collective action emergence, performance, and durability. In addressing this void, I use an in-depth case study approach of two incipient WQT initiatives in the western U.S. to assess if and how the manifestation of external variables considered to be enabling conditions for successful CPR collective action influences the development of emerging WQT programs. This research finds theory regarding CPR collective action enabling conditions useful in understanding the development trajectories of emerging WQT programs. Results suggest that the absence of enabling conditions and strong constitutional rules can undermine the ability of decentralized political systems to support emergent WQT programs. Contrarily, centralized systems with well-defined rules and roles may provide more stable scaffolding for institutional development. These findings demonstrate how the quality of constitutional rules interacts with other external variables, including policy norms, agency allocation, collective choice rules, and social capital, to dictate the evolution and eventual performance of emergent WQT programs and CPR collective action institutions more broadly.